Pharmacy Ethics: Evaluation Pharmacists’ Ethical Attitude - Pooneh Salari Sharif; Mohammadreza Javadi; Fariba Asghari (Journal of Medical Ethics and History of Medicine, 2011)
Alterations in pharmacy practice from prescription dispensing to more patient-centered relationship intensifies the necessity of clinical decision-making. Pharmacists' knowledge as well as ethical reasoning affects their clinical decision-making. Unfortunately in Iran pharmacy ethics did not develop along with medical ethics and special considerations are of major importance. The study was designed to evaluate pharmacists' attitude toward some principles of bioethics.A cross-sectional survey was performed on a sample of Iranian pharmacists attended in continuous education programs in 2010. Based on the pharmacists' attitude toward common ethical problems, 9 Likert-type scale scenarios were designed. A thousand pharmacists were surveyed and 505 questionnaires were filled. For the whole questionnaire the strongly disagree answer was the most ethical answer. On a scale from 1-5 on which 5=strongly disagree, the total score of pharmacists ethical attitude was 17.69 ± 3.57. For easier analysis we considered the score of 1 for agree and strongly agree answers, score of 2 for neutral answers and score of 3 for disagree and strongly disagree answers. The total score in confidentiality for all participants was 4.15 ± 1.45 out of 9, in autonomy 6.25 ± 1.85 out of 9, in non-maleficence 5.14 ± 1.17 out of 6 and in justice was 2.27 ± 0.89 out of 3, however there was no significant difference between men and women in the total score and the score of each theme. The older participants (> 40 years) significantly had lower total score (P< 0.05) as well as the score of each theme (P< 0.05), except for non-maleficence. The work experience showed impact on the pharmacists' attitude toward autonomy and the participants with more than 5 years work experience significantly obtained lower score in this theme.Compiling ethical guidelines and improving pharmacy ethics curriculum is highly critical to provide the best pharmaceutical care and to make clinical decisions in critical situations. Therefore further quantitative and qualitative investigations into finding pitfalls and challenges in this issue are highly recommended.